Needle Stick Injury: A Survey of Five Dental Colleges of Karachi (Medical Forum Monthly, 2024)
Objective:The goal of this research is to find out the rate of needle stick injury in dental practitioners and to check the awareness level among dental health care workers of Karchi.Study Design:Description / Cross-Sectional Study.Place and Duration of Study: The study was conducted at the Jinnah Medical and Dental College. The data was collected from five different dental colleges of Karachi (JMDC, FJDC, DIDC, LCMD and Hamdard) from 15 November 2016 to February 2017.____.Materials and Methods:A 15-item questionnaire was used to collect the data. To examine the research questions, data was collected from 180 respondents comprising of faculty and graduates of the respective dental colleges (JMDC=50, FJDC=58, DIDC=53, LCMD=8 and Hamdard=11).The respondents filled the questionnaires in the presence of the researcher to expedite the process and to answer any potential inquiries. This study used simple random sampling procedure to gather an unbiased data from a large population. The data was stored in excel worksheet and analyzed using SPSS.Results: Out of the 180 dental practitioners evaluated for this research, 58.88% reported with a positive history of needle stick injury. Among these 27.77 % have had the injuries multiple times. At the time of injury, 54.4% of dental practitioners were wearing gloves. 81.11% of practitioners took immunization history, 30% practitioners got their blood screening done after the injury. 86.66% dental practitioners were immunized against Hepatitis B and only 36.66% know their hepatitis B antibody titer.Conclusion:The results of this study indicates that dental students in Karachi have some knowledge of NSIs Nevertheless majority of them failed to recognize appropriate management and reporting of such injuries, therefore, there is a need for improvements in the clinical training, in particular more instructional time devoted to prevention and management of NSIs.